ENHANCEMENT OF ISLAMIC HIGHER EDUCATION MANAGEMENT IN INDONESIA (A Brief Comparation with Melbourne University Management in Australia) - Idri, Idri (JURNAL TADRIS STAIN PAMEKASAN, 2011)
Abstract: Islamic Higher Education is demanded to answer the challenge of  the era by preparing competent, professional, and Islamic graduates. This goal can be achieved through strengthening the management by studying from other universities that have been established and advanced as Melbourne University, the university which belongs to the top 10 colleges top in the world knowing for teaching excellence and research. Islamic Higher Education also need to do some strategic steps to improve the quality of its graduates through the opening excellent programs that have relevance to the needs market labor,  ensuring the availability of funds and building and strengthening cooperation with relevant parties.